Analisis Studi Kelayakan Bisnis di Pabrik Tahu Bu Turwito Purwokerto Timur - Azka Amilatul Fadila; Bay Nana Nurfirdaus; Ike Nur Hasanah; Mely Febriani; Najwah Addina; Raden Muhammad Jallaludin Assayuti; Salma Aulia Ibrahim; Tarisa Esti Kinasih; Sudiro Sudiro (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the feasibility of the Bu Turwito Tofu Factory in East Purwokerto based on marketing, operational techniques, human resources, finance, legality, technology, socio-economic, and environmental aspects. The study used a qualitative approach with a case study method. Data were obtained through observation, semi-structured interviews with the business owner, and documentation, then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results the study indicate that the Bu Turwito Tofu Factory business is still feasible to run and develop. From a marketing aspect, product demand relatively stable despite facing business competition and rising raw material prices. From a legal aspect, the business has Business Identification Number (NIB) and carries out activities in accordance with applicable regulations. The use of technology is still simple, but still able to support the production process. From a socio-economic aspect, contributions the surrounding community are still limited because the business is family-run, while from an environmental aspect, waste management has been carried out through the utilization of solid waste and sedimentation of liquid waste. This research is limited to a single business, so the results cannot be generalized to the entire tofu industry. The findings offer practical implications for MSMEs in improving marketing strategies, technology utilization, and environmental management to support business sustainability. This research provides added value in the form of a comprehensive study of the feasibility of a small-scale tofu industry based on various aspects of a business feasibility study.